Biosynthesis of Copper Nanoparticles Using Chitosan Extracted from Prawn Shells, Characterization and Antimicrobial Activity - Poonguzhali, G; Noorjahan, CM; Keerthana, S (Asian Journal of Biological and Life Sciences)
Marine waste management has been one of the problems having the most significant impact on the environment. Food industrial wastes are an essential environmental contamination source. Research has been carried out to develop methods to convert these wastes into valuable products. Alternatively, this waste can be used to extract chitosan, which possess antimicrobial activity. Hence, an attempt has been made to extract chitosan from the marine waste-prawn shells, synthesize Copper Nanoparticles (CuNPs) using chitosan, and characterize the synthesized CuNPs using Ultra Violet -visible Spectroscopy (UV-Vis), Fourier Transform Infrared spectroscopy (FT-IR) and Scanning Electron Microscopic (SEM) analysis. The antimicrobial activity of the biosynthesized CuNPs against gram-positive and gram-negative bacterial strains: Staphylococcus sp and Pseudomonas sp, and fungal strains: Aspergillus sp and Candida sp were assessed in the present study using the agar well diffusion method. As per the current study’s findings, the zone of inhibition increased with an increase in the sample concentration. It was also observed that the CuNPs showed maximum antibacterial activity towards Pseudomonas sp, followed by Staphylococcus sp, and antifungal activity against Candida sp.
Keywords: Antimicrobial activity; Copper nanoparticles; FT-IR; Prawn Shell; SEM; UV-Visible spectroscopy